2014
DOI: 10.2174/1574887109666140908125158
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Blockers in Pediatric Hypertrophic Cardiomyopathies

Abstract: Congestive cardiac failure accounts for 36% of childhood deaths in hypertrophic cardiomyopathy, and in infants with heart failure symptoms before two years of age, the mortality is extremely high unless treatment with beta-receptor antagonists is instituted. The mechanism of heart failure is not systolic dysfunction, but rather extreme diastolic dysfunction leading to high filling pressures.Risk factors for development of heart failure are a generalized pattern of hypertrophy with a left ventricular posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
0
20
0
6
Order By: Relevance
“…Heart failure accounts for approximately 30% to 40% of childhood deaths in patients with hypertrophic cardiomyopathy (HCM) . There are no FDA‐approved drugs for this condition, which is conventionally treated by β‐blockers in combination with other medications.…”
Section: β‐Blockers For Cardiac Indicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Heart failure accounts for approximately 30% to 40% of childhood deaths in patients with hypertrophic cardiomyopathy (HCM) . There are no FDA‐approved drugs for this condition, which is conventionally treated by β‐blockers in combination with other medications.…”
Section: β‐Blockers For Cardiac Indicationsmentioning
confidence: 99%
“…Atenolol can also be used in HCM, but its use is debatable in patients at risk for arrhythmias and heart failure. Carvedilol is avoided due to the risk of hypotension associated with α‐blockade . A second study reported three deaths in patients not treated with β‐blockers compared to 10 survivors that had received β‐blocker for persistent idiopathic HCM .…”
Section: β‐Blockers For Cardiac Indicationsmentioning
confidence: 99%
See 3 more Smart Citations